STELARR: Sustainable Investments for Large-Scale Rangeland Restoration - International Livestock Research Institute (International Livestock Research Institute, 2024)
The Sustainable Investments for Large-Scale Rangeland Restoration project (STELARR) aims to reverse rangeland degradation and improve rangeland productivity globally through sustainable livestock value chains that benefit pastoralists and other land users.